l-Isoleucine Administration Alleviates DSS-Induced Colitis by Regulating TLR4/MyD88/NF-κB Pathway in Rats - Mao, Xiangbing; Sun, Rui; Wang, Qingxiang; Chen, Daiwen; Yu, Bing; He, Jun; Yu, Jie; Luo, Junqiu; Luo, Yuheng; Yan, Hui; Wang, Jianping; Wang, Huifen; et al. (Frontiers in Immunology, 2022)
Inflammatory bowel disease (including colitis) severely impairs human health. Isoleucine is reported to regulate immune function (such as the production of immunoreactive substances). The aim of this study was to investigate whether l-isoleucine administration might alleviate dextran sulphate sodium (DSS)-induced colitis in rats. In the in vitro trial, IEC-18 cells were treated by 4 mmol/L l-isoleucine for 12 h, which relieved the decrease of cell viability that was induced by TNF-α (10 ng/mL) challenge for 24 h (P < 0.05). Then, in the in vivo experiment, a total of 44 wistar rats were allotted into 2 groups that were fed l-isoleucine-supplemented diet and control diet for 35 d. From 15 d to 35 d, half of rats in 2 groups drank the 4% DSS-adding water. Average daily gain, average daily feed intake and feed conversion of rats were impaired by DSS challenge (P < 0.05). Drinking the DSS-supplementing water also increased disease activity index (DAI) and serum urea nitrogen level (P < 0.05), shortened colonic length (P < 0.05), impaired colonic enterocyte apoptosis, cell cycle and the ZO-1 mRNA expression (P < 0.05), increased the ratio of CD11c-, CD64- and CD169-positive cells in colon (P < 0.05), and induced extensive ulcer, infiltration of inflammatory cells and collagenous fiber hyperplasia in colon. However, dietary l-isoleucine supplementation attenuated the negative effect of DSS challenge on growth performance (P < 0.05), DAI (P < 0.05), colonic length and enterocyte apoptosis (P < 0.05), and dysfunction of colonic histology, and down-regulated the ratio of CD11c-, CD64- and CD169-positive cells, pro-inflammation cytokines and the mRNA expression of TLR4, MyD88, and NF-κB in the colon of rats (P < 0.05). These results suggest that supplementing l-isoleucine in diet improved the DSS-induced growth stunting and colonic damage in rats, which could be associated with the down-regulation of inflammation via regulating TLR4/MyD88/NF-κB pathway in colon.